ESTABLISHMENT OF BASIC APPROACHES TOWARDS FOREIGN POLICY OF CANADA - Olesya Antokhiv-Skolozdra; Khrystyna Sholota (Scientific Journal of Polonia University, 2023)
The article deals with Canada’s foreign policy conceptual orientations on the world arena. Historically, Canada’s endeavor to define its position on both global and regional levels correlated with a number of factors, like the impact of the world super-powers, establishing international organizations (UN, NATO, OSCE), relations with the European countries in the realm of integrational processes on the European continent. The aim of the article is analysing basic principles of foreign policy formation in a post-war period and covering the main approaches: Continentalism, Europeanism and Internationalism. Methods of research involve systemic and chronological approach in theoretical analysis based on transdisciplinary scholars’ investigation. The outcome of the research ensures multilateral approach towards realizing Canada’s role in the world politics. Chronological analysis of transatlantic policy may result as follows: Canadian foreign policy effectively involves alternative external orientations, aimed at diversification of international relations, with the objective of its personal role as both neutral and active representative of international environment.